Analysis of a Steel Bridge Connected with Tunnel Considering Live Project Data Using SAP2000 A Review - Dolly Dewangan; Shubham Dashore; Dr. S. K. Jaiswal (International Journal of Scientific Research in Civil Engineering, 2022)
Majority of the truss bridges in India and abroad are either structurally deficient and/or functionally obsolete. There is a desperate need to enhance the performance of these existing bridges by an appropriate technique which should be economical and with minimum disturbance to the traffic. The aim of the present analytical work is to know the effect of Pre-stressing on the member forces, deflections and total weight of steel of a statically In this paper presenting review of literature related to analysis of steel bridge and tunnels